Deploy any MERN stack app on Azure cloud using CICD pipeline. (Packt Publishing, 2022)
Be a part of a practical and step-by-step course based on full-stack application (MERN) deployment on Azure Cloud with CICD Pipeline using Azure DevOps and other cloud services. About This Video Learn the industry-standard way of building and deploying software using CICD pipelines on Azure DevOps Study end-to-end cycle of software development to deployment to shipping it for production in a controlled automated process Understand how to debug, troubleshoot and monitor your application in real-time In Detail A public cloud is an IT model where on-demand computing services and infrastructure are managed by a third-party provider and shared with multiple organizations using the public Internet. In this course, you will use Microsoft Azure as a cloud-based service to deploy the MERN Stack app. In this course, you will start with understanding on-premises infrastructure, the public cloud, and why we need the public cloud. After that, you will see different types of cloud service providers in the market, different cloud models like IaaS, PaaS, SaaS, and analogies with real-world examples. Next, you will create a free Azure portal account, various services on the Azure portal, and Azure cloud concepts. You will then set up the Azure DevOps organization, projects, and overview of different components of the Azure DevOps dashboard. Next, you will be creating an Azure app service and using it, monitoring and log debugging using application insight, working on continuous integration and continuous deployment pipeline with Azure DevOps, and looking at different Git commands. Finally, you will be testing the application and deleting all services to avoid getting extra costs. By the end of this course, you will have learned how to deploy any MERN Stack app on Azure Cloud with a CICD pipeline using Azure DevOps and other cloud services. Audience This course is designed for anyone who wants to learn the industry way of building and deploying software to production in a controlled automated way. It is also beneficial for the individual who wants to learn the CICD, DevOps way of working using the most popular cloud service that is Azure. You would need the interest to learn the continuous integration and continuous deployment process and enthusiasm to learn about Azure Cloud and Azure DevOps as the only prerequisites.